Improvements in Maximum Likelihood Estimators of Truncated Normal Samples with Prior Knowledge of σ. A Simulation Based Study with Application to Historical Height Samples - Brian A'Hearn; John Komlos (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2003)
Researchers analyzing historical data on human stature have long sought an estimator that performs well in truncated-normal samples. This paper reviews that search, focusing on two currently widespread procedures: truncated least squares (TLS) and truncated maximum likelihood (TML). The first suffers from bias. The second suffers in practical application from excessive variability. A simple procedure is developed to convert TLS truncated means into estimates of the underlying population means, assuming the contemporary population standard deviation. This procedure is shown to be equivalent to restricted TML estimation. Simulation methods are used to establish the mean squared error performance characteristics of the restricted and unconstrained TML estimators in relation to several population and sample parameters. The results provide general insight into the bias-precision tradeoff in restricted estimation and a specific practical guide to optimal estimator choice for researchers in anthropometrics.
urn:nbn:de:bvb:19-epub-51-9
Keywords: C1; C15; C24; 330; truncated least squares; truncated maximum likelihood (TML); simulation methods; bias-precision trade-off; anthropometrics